STUDI TENTANG EFEKTIVITAS MEDIA 3D SKETCHUP DALAM PEMBELAJARAN DI SMK - Alfandi Ziqri (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
The purpose of this study is to learn more about how using SketchUp enhances the educational experience at technical colleges. via examining pertinent research findings and using techniques from literature studies. The primary goal of the study is to quantify the influence that using 3D SketchUp material has on students' comprehension of ideas and skill development. It is believed that these findings would help educators in developing more creative and effective teaching strategies. It is also anticipated that there would be a notable increase in the quality of instruction at vocational schools, better equipping students with the necessary and relevant skills to join the workforce.